ANALISIS YURIDIS KASUS PEMBOBOLAN REKENING PADA BANK MANDIRI - Utami, Istiqlaliyah; Taufiq, Muhammad (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2018)
The identifications of this research are: 1) How did the customers account break into the Depok Branch of Bank Mandiri ?; 2) What is the banks responsibility towards the customer who is a victim of a Bank Mandiri Depok branch burglary? The research method used in this study is a normative juridical approach, namely law is conceived as a norm, rule, principle or dogmas / jurisprudence. The results of this study are: The form of corporate responsibility according to the law in an effort to provide protection for customers who have suffered losses on funds in their accounts can be done in non-litigation and litigation. Non-litigation reports to Indonesian banking mediation institutions, while litigation is through the court. Suggestions for this research, namely: 1) There needs to be a guarantee that means for customers who have entrusted their funds to banks; 2) The government must pay more attention to the activities of banks, especially for Bank Indonesia as a supervisor and supervisor of banking activities so that in this case the bank is more responsible.